Diagnóstico sócio-econômico da indústria madeireira Peracchi, no municipio de Tailândia, estado do Pará - Pokorny, B.; Sousa, R. (Empresa Brasileira de Pesquisa Agropecuária, 2000)
The main objective was to obtain a general impression of the activities of the Peracchi sawmill in the Tailândia region, Pará. This was to assess its potential as a partner in the project ‘Sustainable forest management at commercial scale’, a cooperative project between Embrapa Amaz6nia Oriental and the Center for International Forestry Research. The study included a general description of the region, the stakeholders involved in the use of forest resources, and a financial analysis of sawmill activities. Students of the Agrar Faculty of Pará gathered the field information during two weeks in October 1998. The study showed, that Tailandia was a typical older frontier region, which depended strongly on the forest sector. After more than 15 years of timber harvesting and industrialisation by more than 50 sawmills, the forest resources near the city decreased significantly. As a result of the high number of legal and illegal land use incentives and the strong fluctuation, the system of forest stakeholders was complex and heterogeneous. The Peracchi sawmill was one of the few producing timber for export markets. The enterprise began a government-approved 12 000 ha forest management project and applied conventional logging techniques which had many ecological, economic and social deficiencies. The settlers near the project were not strongly affected. The exploitation of 32 000 m3 year-1 cost about US$15.4 m-3. Motivated by the expectation of certification, the timber enterprise showed a strong interest in participating in the Embrapa/CIFOR project. However, problems include: lack of responsibility and capacity of the enterprise staff; no strategy to ensure the long-term delivery of timber; insufficient documentation; and the danger of illegal invasion of the project area.